Politics in robes? The European Court of Justice and the myth of judicial activism - Andreas Grimmel (Europa-Kolleg Hamburg, Institute for European Integration, 2011)
What characterizes the EU today is that it is not only a multi-level governance system, but also a multi-context system. The making of Europe does not just take place on different levels within the European political framework, executed by different groups of actors or institutions. Rather, it also happens in different and distinguishable social contexts - distinct functional, historical, and local frameworks of reasoning and action - that political science alone cannot sufficiently analyze with conventional and generalizing models of explanation. The European law is such a context, and it should be perceived as a self-contained sphere of argument and action that generates impetus for integration. Therefore, the role of the European Court of Justice in the process of integration may only be adequately captured by examining European law as an independent space of reasoning and action.
Keywords: 330; European Court of Justice (ECJ); Integration through Law; Integration Theory; Regional Integration; Rationalism; Trivial Rationalism; Context Rationality; Context of Law; Context Analysis; Judicial Politics; Europäische Integration; EU-Recht; Rechtsprechung; Justiz; EU-Staaten